2019
DOI: 10.3389/fpsyg.2019.02017
|View full text |Cite
|
Sign up to set email alerts
|

Job Demands as Risk Factors of Exposure to Bullying at Work: The Moderating Role of Team-Level Conflict Management Climate

Abstract: Conflict management climate is an important organizational resource that is theorized to prevent interpersonal frustration from escalating into harsh interpersonal conflicts and even workplace bullying. The present study investigates whether team-level perceptions of conflict management climate moderate the relationship between previously investigated psychosocial predictors of workplace bullying (i.e., role conflicts, workload, cognitive demands) and perceived exposure to bullying behaviors in the workplace. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 67 publications
(105 reference statements)
1
21
0
1
Order By: Relevance
“…The scale assesses intragroup trust and perceived fairness and trust in the department’s dispute resolution and conflict management procedures, including trust in managers’ conflict management skills. These scales have been used in numerous studies, and researchers have reported the scales as reliable with Cronbach’s alpha of 0.81 for climate for conflict management ( Zahlquist et al, 2019 ), Cronbach’s alpha of 0.86 1 for climate for psychological safety ( Koopmann et al, 2016 ), and Cronbach’s alpha of 0.92 2 for intragroup conflict ( Jehns, 1995 ). Example items are “The management handles cases of conflicts well” (conflict management climate), “It is easy to address problems and difficult issues in my work team” (intragroup trust), and “There is jealousy and rivalry between members of my work team” (intragroup conflict).…”
Section: Methods and Analysismentioning
confidence: 99%
“…The scale assesses intragroup trust and perceived fairness and trust in the department’s dispute resolution and conflict management procedures, including trust in managers’ conflict management skills. These scales have been used in numerous studies, and researchers have reported the scales as reliable with Cronbach’s alpha of 0.81 for climate for conflict management ( Zahlquist et al, 2019 ), Cronbach’s alpha of 0.86 1 for climate for psychological safety ( Koopmann et al, 2016 ), and Cronbach’s alpha of 0.92 2 for intragroup conflict ( Jehns, 1995 ). Example items are “The management handles cases of conflicts well” (conflict management climate), “It is easy to address problems and difficult issues in my work team” (intragroup trust), and “There is jealousy and rivalry between members of my work team” (intragroup conflict).…”
Section: Methods and Analysismentioning
confidence: 99%
“…Specifically, we aimed at resources that best match the demands we investigated. Providing task control has been shown to mitigate the negative effects of workloads, [45,46], participation seems suitable to negatively affect role ambiguity [47], and conflict management may be especially helpful in dealing with emotional demands [48,49]. Employees rated their immediate manager on a 5-point Likert-type scale ranging from 1 (strongly disagree) to 5 (strongly agree).…”
Section: Methodsmentioning
confidence: 99%
“…CMC has gained a growing interest among scholars as a developed process (Zahlquist et al, 2019). It is an essential organisational resource that helps buffer interpersonal frustration caused by the workplace's stressful conditions that cause bullying (Einarsen et al, 2018).…”
Section: Conflict Management Climate (Cmc)mentioning
confidence: 99%